Page Turner Ashley Page's inaugural season with Scottish Ballet reviewed - Mackrell, Judith (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Review of Ashley Page's inaugural season with Scottish Ballet. Ever since the death of Peter Darrell in 1987, Scottish Ballet has been floundering in search of a workable identity. PALABRAS CLAVE: Ashley Page, Scottish Ballet, Cheating, Lying, Stealing, Siobhan Davies's White Man Sleeps, Richard Alston's Dangerous Liasons, Stephen Petronio's MiddleSex Gorge.